The predominant role of IgM in grouper (Epinephelus coioides) mucosal defense against ectoparasitic protozoan infection - Mo, Zequan; Lin, Huajian; Lai, Xueli; Dan, Pengbo; Wu, Huicheng; Luo, Xiaochun; Dan, Xueming; Li, Yanwei (Fish & shellfish immunology, 2024)
The skin mucosa of fish is exposed to significant challenges from infectious disease agents due to continuous exposure to the aqueous environment. Interestingly, bony fish have evolved to express a unique IgT, which is absent in terrestrials, that appears to play a predominant role in the mucosal-associated lymphoid tissue of the rainbow trout. Nevertheless, in other IgT-producing fish, it is unclear whether IgM or IgT is primarily responsible for protection against infections of cutaneous tissue. Here, we show that grouper IgM appears quickly within the skin following challenge by the marine parasite, Crytopcaryon irritans. These IgM-class antibodies may arise from local proliferating antibody secreting cells or may infiltrate tissue from the serum in dimer polymer form. Based on details of IgM functional responses, we conclude that grouper IgM plays a predominant role in defense against C. irritans. •Immune fish rapidly increase skin-specific IgM against C. irritans.•C. irritans Challenged groupers exhibit local IgM + B cell expansion and infiltration.•Grouper skin IgM proves crucial in countering C. irritans.